The Gold Digger - Tolsma, Liz (Uhrichsville, OH : Barbour Books, 2020)
"In 1907, shy but loyal Ingrid Storset travels from Norway to support her grieving sister, Belle Gunness, who owns a farm in LaPorte, Indiana. Well-to-do widow Belle, who has lost two husbands and several children, provides Ingrid with enough money to start a small business. But Ingrid is confused by the string of men Belle claims to be interviewing for her next husband. When Nils Lindherud comes to town looking for his missing brother, who said he was going to marry Belle, Ingrid has a sinking feeling her sister is up to no good." --
Keywords: Widows -- Fiction; Missing persons -- Fiction; Women murderers -- Fiction; LaPorte (Ind.) -- Fiction; Detective and mystery fiction; Historical fiction; Christian fiction